Band Method: A Systematic Method Based on Syllables, Rhythm Charts and Motor Coordination of the foot and fingers, which Leads to a Sound Rhythmic Perception - ED SUETA (EDWARD SUETA, 1974)
Rhythm Vocabulary Charts. There are 12 Rhythm Vocabulary Charts Starting on page 30. Recommendation for their use in as follows: Chart 1 - Lesson 1, Chart 2 - Lesson 3, Chart 3 - Lesson 5, Chart 4 - Lesson 7, Chart 5 - Lesson 8, Chart 6 - Lesson 10, Chart 7 - Lesson 12, Chart 8 - Lesson 15, Chart 9 - Lesson 17, Chart 10 - Lesson 19, Chart 11 - Lesson 21, Chart 12 - Lesson 23.